Body modification for enhanced sport performance - Montagna, Gianni (2010)
Body modifications and its presence in human life are as ancient as human life itself. Its achievement can be very different in terms of expression, and with different levels of body aggressiveness. It could be defined as evasive, when something external is used to reach body modification, as in fashion and others forms of art and expression tending to modify human image; or invasive where the body could be permanently modified as in case of body tattooing or physical and flesh modification. Shilling refers to the body as a ―project that being modified helps the construction of a self made human being and a social identity [1]. The natural competition in sports and the demand for better performance forced athletes and their marketing sponsors to propose new products in terms of body resistance and improvement of athlete energy. The aim of this paper is to compare the modifications made in a body due to different kinds of swimsuits used by the same subject and discuss in terms of design what each swimsuit producer understands as the way the design of a swimsuit could contribute for best results. The discussion will also comprehend the main issues regarding swimming: body stabilization through compression, drag reduction and performance endurance.